Implementasi Terapi Orientasi Realita Pada Pasien Waham - Ayun Pranandari; Laili Nur Hidayati; Akrim Wasniyati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Delusions are beliefs held by patients that contradict reality and are entrenched, making them resistant to logical persuasion by others. These beliefs stem from the patient's perception of losing control. A preliminary survey conducted in the maintenance ward of a Mental Hospital revealed cases of schizophrenia with nursing issues related to thought process disorders, particularly delusions of suspicion. The objective of this case study was to assess the efficacy of reality orientation therapy in schizophrenic patients with nursing issues concerning thought process disorders, specifically delusions, within the maintenance ward of a mental hospital. This case study employed a nursing care approach involving assessment, observation, and the implementation of reality orientation therapy over a 6-day period in the maintenance ward of a mental hospital. Following assessment, it was found that the patient expressed suspicion towards family and neighbours, repeatedly stating these beliefs. After implementing strategies targeting delusions I-V, the patient exhibited a return to reality orientation. Through continuous psychiatric therapy, including reality orientation therapy over 6 days, combined with non-pharmacological interventions, delusional behaviours in patients were significantly reduced.